Advanced biofuels to decarbonise European transport by 2030: Markets, challenges, and policies that impact their successful market uptake. (March 2021) - Panoutsou, Calliope; Germer, Sonja; Karka, Paraskevi; Papadokostantakis, Stavros; Kroyan, Yuri; Wojcieszyk, Michal; Maniatis, Kyriakos; Marchand, Philippe; Landalv, Ingvar
Abstract: Advanced biofuels are among the available options to decarbonise transport in the short to medium term especially for aviation, marine and heavy-duty vehicles that lack immediate alternatives. Their production and market uptake, however, is still very low due to several challenges arising across their value chain. So far policy has established targets and monitoring frameworks for low carbon fuels and improved engine performance but has not yet been sufficient to facilitate their effective market uptake. Their market roll-out must be immediate if the 2030 targets are to be met. Analysis in this paper reiterates that the future deployment of these fuels, in market shares that can lead to the desired decarbonisation levels, still depends largely on the integration of tailored policy interventions that can overcome challenges and improve upstream and downstream performance. The work presented aims to i) inform on policy relevant challenges that restrict the flexible, reliable and cost-efficient market uptake of sustainable advanced biofuels for transport, and ii) highlight policy interventions that, have strong potential to overcome the challenges and are relevant to current policy, Green Deal and the Sustainable Development Goals (SDGs).